A 10-Year Retrospective Analysis of Methyl Aminolevulinate Photodynamic Therapy Consultation at the Hospital de Braga - Brito, C (2016)
Photodynamic therapy (PDT) is a well-established treatment for actinic keratosis (AK), basal cell carcinoma (BCC), and Bowen's disease (BD). The object of this study was to describe the results of a retrospective analysis of patients treated with methyl aminolevulinate PDT (MAL-PDT) with red light, over the past decade at the Hospital de Braga (Braga, Portugal).